Development and performance evaluation of a micro anaerobic digestion system for household use. Issue 4 (27th September 2022) - Okaze, Tsubasa; Tada, Chika
Abstract: Currently, sustainable societies require a reduction in general and food waste discharge, which is a major environmental problem. As food waste contains a high moisture content, anaerobic digestion is an effective way to recycle food waste that contains large amounts of moisture. While 70% of industrial food waste is recycled, only approximately 20% of household waste is recycled in Japan. In this study, we developed a micro anaerobic digestion system with a capacity of 30 L and evaluated its basic performance by simulating a daily use situation. Biogas was produced, containing the same amount of methane as other systems. Although no mixing in the fermenter was done, the production efficiency of methane reached approximately at least 60% of the theoretical value of methane gas production for the chemical oxygen demand of the input food waste. Abstract : In this study, we developed a micro anaerobic digestion system with a capacity of 30 L for household use and evaluated its basic performance by simulating a daily use situation. The system could be easily constructed using materials purchased from home improvement stores. Although no mixing in the fermenter was performed, the production efficiency of methane reached approximately at least 60% of the theoretical value of methane gas production for the chemical oxygen demand of the input food waste.